Quality of life in subcutaneous or transvenous implantable cardioverter-defibrillator patients: a secondary analysis of the PRAETORIAN trial - Knops, Reinoud E.; de Veld, Jolien A.; Ghani, Abdul; Boersma, Lucas; Kuschyk, Jürgen; El Chami, Mikhael F.; Bonnemeier, Hendrik; Behr, Elijah R.; Brouwer, Tom F.; Kääb, Stefan; Mittal, Suneet; Pepplinkhuizen, Shari; et al. (Circulation. Cardiovascular quality and outcomes, 2024)
BACKGROUND: - The subcutaneous implantable cardioverter-defibrillator (S-ICD) was developed to overcome the risk of lead-related complications associated with the transvenous implantable cardioverter-defibrillator (TV-ICD). In contrast to the TV-ICD, the S-ICD is a completely extrathoracic device. Subsequently, complications differ between these 2 implantable cardioverter-defibrillators, which might impact patient perceptions of the therapies. This prespecified secondary analysis of the PRAETORIAN trial evaluates differences in quality of life. - METHODS: - The PRAETORIAN trial (A Prospective, Randomized Comparison of Subcutaneous and Transvenous Implantable Cardioverter Defibrillator Therapy) randomized patients with an implantable cardioverter-defibrillator indication, without the need for pacing to S-ICD or TV-ICD therapy. Two questionnaires were collected at baseline, discharge, 12 months, and 30 months. The Duke Activity Status Index measures cardiac-specific physical functioning, and the 36-Item Short Form Health Survey measures physical and mental well-being, with the subscales bodily pain and mental health being of interest in this analysis. Mann-Whitney U tests were used to compare study arms, and a mixed model was used to describe the questionnaire outcomes over time. - RESULTS: - Patients were randomized to S-ICD (n=426) and TV-ICD (n=423). In the S-ICD group, 20% were women versus 19% in the TV-ICD group. The median age was 63 (interquartile range, 54-69) years in the S-ICD group versus 64 (interquartile range, 56-69) years in the TV-ICD group. There were no significant differences in the Duke Activity Status Index and 36-Item Short Form Health Survey subscales for bodily pain and mental health between the groups at any time point. Patients with a shock in the last 90 days had significantly lower scores for social functioning (P=0.008) and role limitations due to emotional problems (P=0.001) than patients without a shock, but this effect did not differ between treatment arms. - CONCLUSIONS: - In a large randomized cohort of patients with an S-ICD or TV-ICD, no difference in overall quality of life was observed. However, implantable cardioverter-defibrillator shocks resulted in a reduction in quality of life, regardless of the device type or appropriateness. - REGISTRATION: - URL: https://www.clinicaltrials.gov; Unique identifier: NCT01296022.
Online veröffentlicht: 19. November 2024
Gesehen am 20.05.2025